Complex Regional Pain Syndrome (CRPS/RSD) and Neuropathic Pain: Role of Intravenous Bisphosphonates as Analgesics - Jennifer Yanow; Marco Pappagallo; Letha Pillai (The Scientific World Journal)
Neuropathic pain is a sequela of dysfunction, injuries, or diseases of the peripheral and/or central nervous system pain pathways, which has historically been extremely difficult to treat. Complex regional pain syndrome (CRPS) types 1 and 2 are neuropathic pain conditions that have a long history in the medical literature but whose pathophysiology remains elusive and whose available treatment options remain few. While an exact animal model for CRPS doesn't yet exist, there are several animal models of neuropathic pain that develop behaviors of hypersensitivity, one of the hallmark signs of neuropathic pain in humans.